Analysis of classification of text documents according to the content using machine learning methods: Analysis of classification of text documents according to the content using machine learning methods - Saidov , Doniyor; Eshbadalov, Sirojiddin (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. This paper is dedicated to the classification of text documents according to their content. There is given information for preliminary processing and selection of algorithms to classification of textual documents.